2019
DOI: 10.2174/1381612825666181226151959
|View full text |Cite
|
Sign up to set email alerts
|

Novel Oral Anticoagulants in Peripheral Artery Disease: Current Evidence

Abstract: Background: Peripheral artery disease is a common manifestation of systemic atherosclerosis which strongly correlates to cardiovascular morbidity and mortality. In addition, the progression of peripheral artery disease leads to an increased risk of limb loss. In order to reduce these events, the benchmark of treatment and research over the last years has been the antiplatelet therapy which aims at inhibition of platelet aggregation. Over the last years, new studies combining antiplatelet agents in different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…As previously mentioned, many patients requiring angiogenesis-promoting therapies for central/peripheral vasculopathy and chronic wounds, who would greatly benefit from new generation bioactive treatments such as hypoxia preconditioned blood-derived secretomes, routinely receive OA [ 27 , 40 , 41 ]. A better understanding of the effects that OA administration may have on the angiogenic potential of blood-derived secretomes is therefore a key prerequisite for advancing their clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, many patients requiring angiogenesis-promoting therapies for central/peripheral vasculopathy and chronic wounds, who would greatly benefit from new generation bioactive treatments such as hypoxia preconditioned blood-derived secretomes, routinely receive OA [ 27 , 40 , 41 ]. A better understanding of the effects that OA administration may have on the angiogenic potential of blood-derived secretomes is therefore a key prerequisite for advancing their clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet inhibition plus low-dose anticoagulant would depend on status to balance ischemic and bleeding risks when selecting type, dose, and intensity of antithrombotic treatment for PAD. [21][22][23] Our study has some limitations. In this meta-analysis, the number of RCT trials was low and major bleeding events are a severe problem for antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Antiplatelet therapy has been the mainstay of treatment in the past few years, but the incidence of cardiovascular events remains high. Studies have shown that new oral anticoagulants combined with aspirin can improve the patient benefit rate [22]. Therapeutic doses of warfarin reduce recurrent ischemic events after myocardial infarction but also increase the risk of bleeding [23].…”
Section: Discussionmentioning
confidence: 99%